Impact of Capacity Building and Managerial Support on Employees' Performance: The Moderating Role of Employees' Retention. (July 2019) - Wassem, Muhammad; Baig, Sajjad Ahmad; Abrar, Muhammad; Hashim, Muhammad; Zia-Ur-Rehman, Muhammad; Awan, Usman; Amjad, Fiza; Nawab, Yasir
The purpose of this study is to investigate the effects of capacity building and managers' support on employee performance in the textile industry. Moreover, this article also investigates the moderating effect exerted by employee retention on the effects of capacity building and managers' support on employee performance. Data were collected through a convenience sampling technique. A self-administered questionnaire survey was conducted for data collection. Two hundred copies of questionnaires were distributed, and data were collected from the lower to middle-level employees who are working in the textile sector of Pakistan. SPSS 23 and SmartPLS-3 software were used for analysis. The results indicate that capacity building has a positive and significant impact on employee performance. In contrast, managerial support has an insignificant impact on employees' performance. However, the impact of capacity building and managerial support on employee performance is positive and significantly moderated by employee retention. The results of this study will motivate owners/policymakers to invest in capacity building to enhance their organizational performance/productivity.